Here comes Peter Cottontail - Kaye, Danny; Frees, Paul.; Gardner, Joan, 1914-1999; Kasem, Casey; Price, Vincent, 1911-1993.; Rankin, Arthur, Jr.; Bass, Jules; Friedrich, Otto, 1929-1995.; Friedrich, Priscilla; Classic Media, Inc.; Sony Wonder (Firm) ([United States] : Classic Media ; New York : Manufactured by Sony Wonder, 2005)
Peter Cottontail wants to be the chief Easter Bunny and everyone in April Valley agrees, except for Evil Irontail. Peter must deliver more eggs than his rival to earn the top spot and save Easter for children everywhere.
Videodisc release of the 1971 television production.
"The original TV classic"--Container.
Teleplay based on the book, "The Easter bunny that over slept," by Priscilla and Otto Friedrich.
Special features: "Peter Rabbit & other tales" animated stories; "Peter Cottontail, the movie" sneak peek; "Peter Cottontail, the movie" music video; "Here comes Peter Cottontail" sing-along songs.
Music and lyrics by Steve Nelson and Jack Rollins ; musical director, Maury Laws.
Told and sung by Danny Kaye ; featuring the voice talents of Paul Frees, Joan Gardner, Casey Kasem, Iris Rainer, Greg Thomas, Jeff Thomas, Vincent Price (as Irontale).
Keywords: Easter stories; Rabbits -- Juvenile drama; Easter eggs -- Juvenile drama; Children's films; Feature films; Animated films; Films for the hearing impaired